Tanggung Jawab Orang tua Terhadap Pendidikan Anak Sekolah minggu Jenjang Batita Di Masa Pandemi Covid-19 - Defi Stenly Nenkeula (Peneliti.net, 2021)
The purpose of this study was to see the responsibility of parents in the education of toddlers for Sunday school children during the Covid-19 pandemic. As we all know that Christian Religious Education is very basic for Christian families and it has become a Christian tradition to continue to educate and be educated since they are still in the womb and forever. Church formal education, namely Sunday school, is part of Christian Religious Education itself. Therefore, education from parents and teachers is needed for toddlers who are important assets of the church and become a generation that can manifest God's love for the world. The research method used in this study used a qualitative descriptive approach. The research subjects were Sunday school children from 0-3 years old in the GPM Tual congregation. As for the results of his research show that from the reality that occurs in the GPM Tual congregation that Sunday school children at the toddler level aged 0-3 years, there is a lack of parental responsibility in seeing children's education, especially in formal Sunday school church education, so parents need to have more love love children so that they can share time with children in educating and guiding them. This concludes that the importance of people's responsibility during the Covid-19 pandemic for toddler-level Sunday school children. This would explain that parents are the main and especially teachers for children in the family after other teachers such as teachers, caregivers and other mentors. For this reason, the character building of children in formal and non-formal education is very important in order to show a good and pleasing image of God.